PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELEJARAN PENDIDIKAN PANCASILA DENGAN MODEL ROLE PLAYING DI KELAS V SDN 12 BUKIT CANGANG KOTA BUKITTINGGI - M. Andrean Fernandes; Atri Waldi; Tiok Wijanarko; Arwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of fifth-grade students at SDN 12 Bukit Cangang, Bukittinggi City. These problems are caused by the learning process remains teacher-centered, relies heavily on lecture-based methods, and shows minimal active student participation in classroom activities, resulting in low learning outcomes across three aspects: attitudes, knowledge, and skills. The purpose of this study is to describe the improvement in student learning outcomes through the application of the Role Playing model in fifth-grade Pancasila Education at SDN 12 Bukit Cangang, Bukittinggi City, covering aspects of teaching module design, learning implementation, and student learning outcomes. The study employed Classroom Action Research (CAR) using both qualitative and quantitative approaches. It was carried out over two cycles, where the first cycle included two meetings and the second cycle consisted of one meeting, in the first semester of the 2025/2026 academic year. The research subjects were 17 fifth-grade students at SDN 12 Bukit Cangang. Data were gathered through observation, tests, and documentation, and subsequently analyzed using descriptive methods. The results showed significant improvements in all observed aspects. The design of The teaching module improved from 83.3% (Good) in Cycle I, Meeting I, to 95.8% (Very Good) in Cycle II. Teacher performance rose from 77.2% (Fair) to 95.4% (Very Good), while student participation increased from 75% (Fair) to 95.4% (Very Good). Learning outcomes in the attitude aspect increased from an average of 71.69 to 83.45, knowledge from 65.88 to 90, and skills from 74.26 to 91.17, with 100% completion across all three aspects in Cycle II.Based on these results, It can be concluded that the consistent and effective application of the Role Playing model is able to comprehensively enhance students’ learning outcomes in Pancasila Education for fifth-grade students at SDN 12 Bukit Cangang, Bukittinggi City.